Infection, cure and egg reduction rates of soil-transmitted helminth infections after anthelminthic drugs treatment among school children in Kokap, Yogyakarta, Indonesia - Fitria Siwi Nur Rochmah; Elsa Herdiana Murhandarwati; Sri Sumarni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
The prevalence of helminthiasis on primary school children in Indonesia is high, around 40-60%. This study aims to assess the impact of treatment and predictors of soil-transmittedhelminth (STH) infections at 3 months after treatment. Population of this study wasstudents of a primary school in Kokap (Sekolah Dasar Negeri/SDN Gunung Agung), KulonProgo, Yogyakarta, determined based on the inclusion and exclusion criteria (n = 65).Stool samples examined using Kato Katz method. Students infected with STH were givenappropriate treatment and stool samples were collected again to determine cure rate (CR)and egg reduction rate (ERR) at 2 week post-treatment and at 3 months post-treatmentto determine incidence of re-infection, new infection or failed treatment. Informationon personal hygiene and sanitation were collected by interview with students of SDNGunung Agung. Treatment with pyrantel pamoat was effective against hookworm andAscaris lumbricoides with CR of 100% and ERR of 100% while treatment with albendazolwas ineffective against Trichuris trichiura (CR = 12.8%, ERR = 62.4%) though theWilcoxon test for T. trichiura showed a significant reduction egg count (epg) before and2 week after treatment (p<0.05). The overall infection rate at 3 months after treatmentwas 35.4% with cases of re-infection, new infection and untreated cases. This result wasnot significantly different with infection rate before treatment (p>0.05). The existence ofdouble infection before treatment showed p value <0.05 (OR = 2) with the prevalence ofSTH infections 3 months after treatment. Bivariate analysis between personal hygiene andenvironmental sanitation with the prevalence of STH infections 3 months after treatmentwas obtained p value >0.05. Presence of re-infection, new infection and untreated casesconfirms that an integrated approach is necessary to control STH infection in Kokap,Kulon Progo, Yogyakarta.